2017
DOI: 10.1089/cyber.2016.0505
|View full text |Cite
|
Sign up to set email alerts
|

Sense of Community on Twitter and Instagram: Exploring the Roles of Motives and Parasocial Relationships

Abstract: Although research has explored the ways in which people form virtual communities to converse about media figures, television shows, and similar topics, little research has examined the link between virtual communities and the parasocial relationships (PSRs) that are often the focus of these conversations and users' experiences in those virtual communities. We examined sense of community (SOC) on Twitter and Instagram as a function of users' motives for use and users' PSR on the sites. In addition to examining … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
50
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(54 citation statements)
references
References 13 publications
1
50
0
3
Order By: Relevance
“…Social networks offer a unique opportunity to spur socialisation at university. The social interaction processes and patterns of information sharing that can develop on Twitter have a positive influence on the sense of community generated among students (Blight, Ruppel, & Schoenbauer, 2017). As Mamonov, Koufaris, and Benbunan-Fich (2016) assert, social interaction has a positive relationship with the sense of community on social networks.…”
Section: Literature Reviewmentioning
confidence: 98%
“…Social networks offer a unique opportunity to spur socialisation at university. The social interaction processes and patterns of information sharing that can develop on Twitter have a positive influence on the sense of community generated among students (Blight, Ruppel, & Schoenbauer, 2017). As Mamonov, Koufaris, and Benbunan-Fich (2016) assert, social interaction has a positive relationship with the sense of community on social networks.…”
Section: Literature Reviewmentioning
confidence: 98%
“…In studies that have examined online parasocial interaction, some scholars have focused on how parasocial relationships through social media engagements with celebrities can influence fan's attitudes and behaviors. Specifically, scholars have found that parasocial E-ISSN: 2289-1528 https://doi.org/10.17576/JKMJC-2019-3501-19 relationships with celebrities affect social media users in many ways, e.g., in fostering a heightened sense of interpersonal closeness (Frederick, Choong, Clavio & Walsh, 2012), increased sense of community (SOC) in online communities formed by Twitter and Instagram users (Blight, Ruppel & Schoenbauer, 2017), and can lead to behavioural intention to purchase products or services endorsed by the celebrity on social media (Schroath, 2016), and even elevated levels of perceived brand credibility in the brands endorsed by the celebrities on social media (Chung & Cho, 2014). Parasocial relationship with television stars can even influence the intention to watch the television show in the near future for their loyal fans who follow them on Twitter (Tengku Siti Aisha & Aini Maznina, 2017).…”
Section: Parasocial Interaction and Social Mediamentioning
confidence: 99%
“…Thus, posting a photo and receiving likes and positive comments aids individuals' psyche. Blight, Ruppel, and Schoenbauer (2017) meanwhile examined sense of community on Twitter and Instagram as a function of users' motives for use, finding those linkages a stronger motive of Instagram interaction than interactivity on Twitter.…”
Section: Instagram and Social Sharingmentioning
confidence: 99%